Fluorescence in situ hybridization test for detection of endometrial carcinoma cells by non‐invasive vaginal swab. Issue 3 (10th January 2023) - Weimer, Jörg; Hüttmann, Martje; Nusilati, Asiyan; Andreas, Svenja; Röseler, Jona; Tribian, Nils; Rogmans, Christoph; Stope, Matthias Bernhard; Dahl, Edgar; Mustea, Alexander; Stickeler, Elmar; Hedemann, Nina; et al.
Abstract: Endometrial cancer (EC) is the most common gynaecological malignancy with increasing incidence in developed countries. As gold standard, hysteroscopy confirms only 30% of suspected ECs. The detection of EC cells in the vagina by fluorescence in situ hybridization (FISH) after a smear test could reduce invasive procedures in the future. Using array‐based comparative genome hybridization (aCGH) on 65 endometrial carcinomas, most frequently imbalanced regions of the tumour genome were identified. Bacterial artificial chromosomes were used to generate FISH‐probes homologue to these human regions. The FISH test was hybridized on swabs specimens collected from the vaginal cavity. Samples from six patients without EC were selected as a negative control and on 13 patients with known EC as a positive control. To distinguish between benign and EC cases, the cut‐off value has been defined. A first validation of this EC‐FISH Test was performed with swabs from 41 patients with suspected EC. The most common genomic imbalances in EC are around the CTNNB1, FBXW7 and APC genes. The cut‐off is defined at 32% of analysed cells without diploid signal pattern. This differs significantly between the positive and negative controls ( p < 0.001). In a first validation cohort of 41 patients with suspected EC, the EC‐FISH Test distinguishes patients with and without EC with a sensitivity of 91% and a specificity of 83%. The negative predictive value is 96%. This is the first report of a non‐invasive EC‐FISH Test to predict EC in women with suspected EC.